Chlamydial conjunctivitis: prevalence and serovar distribution ofChlamydia trachomatisin adults. Issue 9 (September 2015) - Petrovay, Fruzsina; Németh, István; Balázs, Andrea; Balla, Eszter
Abstract : N/A: The extragenital manifestation of Chlamydia trachomatis infection frequently results in non‐specific conjunctivitis among sexually active adults. The aims of the present study were to determine the prevalence of C. trachomatis, to describe the distribution of serovars among patients with conjunctivitis and to characterize the relationship between the prevalence and patient demographics such as age and gender. A total of 245 conjunctival specimens were screened for C. trachomatis DNA targeting the plasmid gene. Serovar determination of the C. trachomatis ‐positive specimens was carried out by an omp1 PCR‐based RFLP analysis method. Statistical analysis was done using a generalized linear model. C. trachomatis was detected in 53 cases (21.6 %) of adult conjunctivitis. Molecular genotyping differentiated seven distinct urogenital serovars, the most prevalent being serovar E (16/53), followed by F (15/53), D (6/53), K (6/53), G (4/53), H (4/53) and J (2/53). Statistical analysis showed higher C. trachomatis prevalence in the younger age groups, and this peaked at younger age in women than in men. The high prevalence of this pathogen found in ocular samples should alert ophthalmologists to focus on the role of C. trachomatis in adult conjunctivitis. The serovar distribution indicated that ocular chlamydial infections usually have a genital source. Nevertheless, conjunctivitis might be the only sign of this sexually transmitted infection. Further comparative genotyping of C. trachomatis in ocular and genital specimens might give more detailed epidemiological information about the aetiology of the disease.